Study on effects of technological factors on fabrication and modification of Zn plating - Mai Van, Phuoc; Phan Thị Dinh; Phạm Thị Phượng; Vũ Minh Thành (Journal of Military Science and Technology, 2022)
This work presents research on the effects of current density and fabrication time on Zn coating from a solution containing 65 g/L ZnO, 120 g/L NaCN, 5 g/L Na2S, 20 g/L NaOH and 5 g/L glycerol. Results showed that at cathode current density ic = 1 ¸ 3 A/dm2, coating time 30 ¸ 60 minutes, and solution temperature 25 ¸ 30 ℃, the obtained coating had a smooth, glossy surface and bright color. Coated sample was subsequently modified in BT-30HL solution for 10 ¸ 60 seconds, at a temperature of 25 ¸ 30 ℃ to achieve passivated coating, containing small and homogeneous phosphate salt crystals distributed evenly on the surface. The passivated zinc coating layer had high corrosion resistance, and was able to withstand a salt mist environment according to TCVN 7699-2-52:2007 standard at harsh level 3, corrosion rate was very minor, at 0.0162 mm/year.